When abortion was a crime : women, medicine, and law in the United States, 1867-1973 - Reagan, Leslie J. (University of California Press, 2022)
"The definitive history of abortion in the United States, with a new preface that equips readers for what's to come. When Abortion Was a Crime is the must-read book on abortion history. Originally published ahead of the thirtieth anniversary of Roe v. Wade, this award-winning study was the first to examine the entire period during which abortion was illegal in the United States, beginning in the mid-nineteenth century and ending with that monumental case in 1973. When Abortion Was a Crime is filled with intimate stories and nuanced analysis, demonstrating how abortion was criminalized and policed--and how millions of women sought abortions regardless of the law. With this edition, Leslie J. Reagan provides a new preface that addresses the dangerous and ongoing threats to abortion access across the country, and the precarity of our current moment. While abortions have typically been portrayed as grim "back alley" operations, this deeply researched history confirms that many abortion providers--including physicians--practiced openly and safely, despite prohibitions by the state and the American Medical Association. Women could find cooperative and reliable practitioners; but prosecution, public humiliation, loss of privacy, and inferior medical care were a constant threat. Reagan's analysis of previously untapped sources, including inquest records and trial transcripts, shows the fragility of patient rights and raises provocative questions about the relationship between medicine and law. With the right to abortion increasingly under attack, this book remains the definitive history of abortion in the United States, offering vital lessons for every American concerned with health care, civil liberties, and personal and sexual freedom."--